From Domestic Setting to Display Space: The Evolution of the Foster Associates’ Work Spaces and Methodology - Gabriel Hernández (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The Foster Associates team has been depicted, among many other identities, as superheroes, a rock-band, tandem riders and a football team. Founded by Norman and Wendy Foster, their collective working methodology has become one of the practice’s primary trademarks. This article explores how the studio’s spatial configuration, in its many iterations from the beginning of the 1960s to the early 1980s, has enhanced innovation, team interactions and individual contributions.The practice’s distinctive design philosophy has been mirrored in the many workspaces that have housed the practice, from its domestic setting in London’s Hampstead Hill Gardens, to its current main office space in Battersea. In this progression, the Fitzroy Street studio, where Foster Associates operated for almost a decade (1972-1981), is the best example of how a series of design concepts influenced teamwork and produced the successful merging of a ’showroom office’ and a ’mock-up office’. The office at Fitzroy Street was conceived as a lab that rethinks the built environment, blending individual contributions to support a collaborative working methodology that enhanced collective multidisciplinary dynamics.